Uji Mutu Fisiologis Benih pada Beberapa Varietas Sorgum (Sorghum bicolor L.) dengan Umur Simpan yang Berbeda - Akbar, Kemal Hidayat; Widiastuti, Mira Landep; Azizah, Elia; Samaullah, M Yamin (JURNAL AGROPLASMA, 2024)
Sorghum (Sorghum bicolor L.) is one of the alternative food crops that is still rarely cultivated in Indonesia. The development of sorghum cultivation can be started by using quality seeds. The storage processof sorghum seeds must be well maintained, because sorghum seeds contain high carbohydrates and proteins that are hygroscopic in nature so that they affect the moisture content and physiological quality of the seeds. The purpose of this study was to obtain a nappropriates helf life for several varieties of sorghum. The research was conducted at the BRIN Appropriate Technology Laboratory, from June to August 2023. The research method used was a factorial Completely Randomized Design (CRD) experiment consisting of 2 factors, namely the shelf life period and sorghum varieties with 4 replications, so the rewere 24 experiments. The first factoris variety which consists of 3 levels, namelyv1 = Soper 6, v2 = Suri 3, and v3 = Kawali. The second factor was shelf life consisting of 2 levels, namelys1 = 1year and s2 = 2 years. The effect of the treatment was tested by analysis of variance and if the F test at 5% was significant, it was followed by Duncan Multiple Range further test (DMRT). The results of the experiment showed that there was an interaction between different types of varieties and shelf life on the observation parameters of moisturecontent, germination, vigorindex, growth speed, and electrical conductivity and there was no interaction on the parameter of dry weight of normal sprouts. Atstorage age, the best percentage of moisture content is 9,51%, germination power is 94,62%, vigor index is 55,63%, growth speed is 41,30%, and electrical conductivity is 25,32%. Keywords: seed physiological quality, shelflife, sorghum